Virtual Reality as a Tool for Student Orientation in Distance Education Programs: A Study of New Library and Information Science Students. - Valenti, Sandra; Lund, Brady; Ting Wang (Information Technology & Libraries, 2020)
Virtual reality (VR) has emerged as a popular technology for gaming and learning, with its uses for teaching presently being investigated in a variety of educational settings. However, one area where the effect of this technology on students has not been examined in detail is as tool for new student orientation in colleges and universities. This study investigates this effect using an experimental methodology and the population of new master of library science (MLS) students entering a library and information science (LIS) program. The results indicate that students who received a VR orientation expressed more optimistic views about the technology, saw greater improvement in scores on an assessment of knowledge about their program and chosen profession, and saw a small decrease in program anxiety compared to those who received the same information as standard textand- links. The majority of students also indicated a willingness to use VR technology for learning for long periods of time (25 minutes or more). The researchers concluded that VR may be a useful tool for increasing student engagement, as described by Game Engagement Theory.